(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This experimental study investigates cardiovascular and muscular endurance among students pursuing a Bachelor of Science (BS) degree in the Department of Sports Sciences and Physical Education (DSS&PE) Mohi-ud-Din Islamic University (MIU) Nerian Sharif, Azad Kashmir. The research, conducted during the initial semester of 2023, faced challenges in assessing upper body muscular endurance, abdominal muscular endurance, and cardiovascular fitness for a total population of 44 students. Adopting L. R. Gay’s guidance, a 20% sample (10 students) was selected using a simple random sampling technique to ensure representativeness. Three separate tests, namely the Harvard step test for cardiovascular fitness and push-ups and curl-ups from the standardized FITNESGRAM test for upper body and abdominal muscular endurance, respectively, were employed. The tests were standardized with established parameters. Focusing on health-related components from a total of 11 physical fitness elements, the study revealed poor cardiovascular fitness among students, warranting special attention, equipment, and training methods. Upper body endurance, assessed through push-ups, indicated a poor fitness zone, while abdominal muscular endurance was found to be average. Recommendations include increased attention to relevant equipment for enhancing muscular endurance and positive changes in practical classes within the SS&PE department. Additionally, students may improve their muscular endurance through overworking and overloading, fostering stronger muscles and increased endurance. In conclusion, students within the SS&PE domain demonstrated poor cardiovascular and upper body muscular endurance, with average abdominal muscular endurance. These findings underscore the importance of targeted interventions and fitness programs to enhance specific areas of physical fitness among the students.